Lipid Profile and Antihypertensive Drugs - Abdul-Khader, Abdul-Khader A. (AL-Kindy College Medical Journal, 2009)
Background: Hypertension and dyslipidemia are cardiovascular risk factors that commonly coexist . Objective : To evaluate the effects of ß - blocker (Atenolol) , ACE inhibitor (Captopril) calcium Channel blocker (Nefidipin ) and diuretics on serum lipid profiles . Method: Thirty untreated hypertensive and 147 hypertensive patient treated with these antihypertensive drugs, attending different public health clinics in Basrah pronivce were enrolled in this study . Serum lipid profile were determined enzymaticaly using kits from BioMerieux, France . Result : The study has revealed that ß-blocker do not significantly affect total cholesterol ( TC ) and LDLcholesterol , but increase significantly triglyceride (TG) and VLDL – cholesterol and decrease HDL – cholesterol. Diuretics causes a significant elevation of TG with generally no significant changes in TC , LDL – cholesterol , VLDL – cholesterol and HDL-cholesterol. ACE inhibitor and calcium channel blockers appears to have no significant effect on plasma lipids . Conclusion :It may important to measure blood lipid levels to identify pre-existing hyperlipidemia before starting the antihypertensive therapy and to select antihypertensive agent that will not influence the lipid profile or interfere with the therapy of hyperlipidemi